PAH radiative cooling and fragmentation kinematics studied within an electrostatic ring. (29th January 2015) - Brédy, R; Ortéga, C; Ji, M; Chen, L; Bernard, J; Allouche, A R; Joblin, C; Cassimi, A; Martin, S
Abstract: Radiative cooling of polycyclic aromatic hydrocarbon (PAH) cations has been studied using a compact electrostatic ion storage ring, the Mini-Ring, in a time range up to 8 ms. The time evolution of the internal energy distribution of the ensemble of stored ions shows evidences of fast cooling which is attributed to the fluorescence from thermally excited electronic states. The internal energy distribution was probed by inducing unimolecular dissociation with single-photon absorption at given storage times. Information on the fragmentation kinematics and the dissociation channels were obtained by analyzing the image of the emitted neutrals detected with a time and position sensitive detector.